Evaluation of some fungicides for inhibiting proteolytic fungi isolated from leather binding of a historical manuscript dated back to the Mamluk period - Mostafa Abdel-Hamied; Ahmed A. M. Abdelhafez; Rania F. Ahmed; Sherif H. Abd-Alrahman; Gomaa Abdel-Maksoud (Heritage Science)
Abstract Fungi have an essential role in deterioration of historical leather bindings, leading to major problems in the preservative state of these artifacts. This study aims to evaluate the efficiency of some fungicides and nanoparticles materials against fungal activity of historical leather bindings. Historical leather binding from an illuminated paper manuscript dating back to the Mamluk period (1250–1516 AD) at the Al-Azhar library, Cairo, Egypt was examined for fungal infection, and isolation. Results of the present study showed, 21 fungal isolates were isolated and identified using morphological and molecular techniques as Alternaria alternate (5%), Aspergillus fumigatus (43%), Aspergillus niger (43%), Aspergillus terrus (5%), and Penicillium chrysogenum (5%). All fungal isolates exhibited proteolytic activity. Aspergillus niger (2–7) and Aspergillus fumigatus (3–4) achieved the highest proteolytic activity amongst obtained fungal strains. Seven fungicides, difenoconazole, propiconazole, azoxystrobin, pyraclostrobin, boscalid, dimethomorph, and thiophanate-methyl as individual active ingredient and two mixtures [difenoconazole combined with propiconazole (1:1)] and [boscalid combined with pyraclostrobin (2:1)] were evaluated at different concentrations against A. fumigatus and A. niger. Additionally, the effect of titanium and silicon dioxides nanoparticles, against the highest proteolytic fungi A. fumigatus and A. niger was evaluated. The fungal growth inhibition was assessed by the disc diffusion method (DDM). The results revealed that individual or mixed boscalid and pyraclostrobin fungicides at 300 ppm achieved the highest inhibition activity against A. fumigatus, but the linear diagram showed that individual boscalid and pyraclostrobin fungicides at 200 ppm was the ideal concentration for application with the leather samples in the future study. The mixture of boscalid + pyraclostrobin (2:1) exhibited the best preservation effect against A. niger achieving 65.9%, and 82.4% microbial inhibition at 150, and 300 ppm, respectively, followed by individual boscalid fungicide.